Bioincompatible Impact of Different Peritoneal Dialysis Fluid Components and Therapeutic Interventions as Tested in a Rat Peritoneal Dialysis Model. (2nd August 2011) - Stavenuiter, Andrea W. D.; Farhat, Karima; Schilte, Margot N.; ter Wee, Piet M.; Beelen, Robert H. J.
Abstract : Peritoneal dialysis (PD) is associated with functional and structural changes of the peritoneal membrane. In this paper, we describe the impact of different factors contributing to peritoneal incompatibility of PD fluid installation including presence of a catheter, volume loading, and the PD fluid components itself. These factors initiate recruitment and activation of peritoneal immune cells such as macrophages and mast cells, as well as activation of peritoneal cells as mesothelial cells in situ. We provide an overview of PD-associated changes as seen in our rat PD-exposure model. Since these changes are partly reversible, we finally discuss therapeutic strategies in the rat PD model with possible consequences of long-term PD in the relevant human setting.